Combination effects of ultra-high pressure and temperature on the physical and thermal properties of ostrich meat sausage (yor) - Thawatchai Supavititpatana (2018)
Ostrich meat sausages (yor) were subjected to ultra-high pressures of 300, 500 and 700 MPa for 40 and 60 min at 40 and 60 °C. Subsequently the physical properties of the products, colour, released and expressible water, gel strength and stress relaxation as well as their thermal characteristics (by differential scanning calorimeter, DSC) were determined. The effects of pressure, temperature and holding time significantly influenced the L*, a*and b*values. The amount of released plus expressible water significantly decreased with increasing pressure, temperature and holding time. The gel strength and equilibrium stress increased with increasing severity of treatment. DSC thermograms indicated that pressures of 700 MPa yielded gel networks involving completely denatured protein with the ability to retain water. © 2007 Elsevier Ltd. All rights reserved.